Strategies in developing a balanced mutual recognition agreement: internationalization and outcomes - Raja Kasim, Raja Suzana (2011)
The Malaysian international education sector has developed enormously throughout the past decade and Malaysia is becoming a centre of quality educational in the region The country currently has more than 50,000 international students from more than 100 countries (MOHE, 2011). Malaysia offers quality international education at an affordable cost. Besides the fairly low cost of education, many choose to study here because they recognize Malaysia as an ideal opportunity to expand their Asian network and relationships (MOHE, 2011) The onset of the 21st century along with increasing globalization has inevitably altered the social, political, and economic landscapes of countries in the world (Raja Suzana, 2010). The rapid advancement of information system technologies such as the internet and telecommunication tools has permanently changed the very foundation of education and acquisition of knowledge (Raja Suzana, 2010) In such a scenario the resourceful handling of knowledge has appeared as a cornerstone of competitive edge It has been frequently underscored that the efficient management of knowledge is more treasured and more influential compared to other factors and means of economic production (Stewart, 1997). A logical consequence of the changing situation is the implications on educational institutions notably at the tertiary level (Raja Suzana, 2010). Confronted with the stark realities of the changing role of education and the acquisition of knowledge, the education systems in many countries have realigned their education systems to face the new challenges of the new knowledge economy (Raja Suzana, 2010). The situation in Malaysia is no different. Indeed, the Ninth Malaysia Plan exemplifies one of the most noteworthy government blueprints in its effort of shaping a continuous economic progress and improved socioeconomic conditions for the people (Raja Suzana, 2010) It is quite evident that knowledge has become more crucial among public and private organizations including the institutions of higher learning (IHLs) (Morshidi Sirat, 2009). It has also been pointed out that technological developments also hold the prospect to drastically alter the nature of provision, delivery and trade in higher education (Radin Umar, 2008) The situation of higher education since the 1990s can be best characterized as ever changing with internationalization and globalization (Morshidi Sirat, 2009).